Mathematical modeling of physical processes in test complexes of electric machines - D. I. Popov (Омский научный вестник)
The article is devoted to the study of the issue of creating energy-efficient test complexes designed for testing induction motors and DC motors by the method of mutual load. For the considered schemes, mathematical models are made, allowing to study static and dynamic modes of operation both in the test and load machines, and in the elements of the frequency converter. The practical value of the obtained mathematical models is that they can be used in the design process of new test complexes to determine the necessary parameters of the equipment at the known parameters of the tested motors, as well as to simulate transition process in the electrical circuits of the test scheme in order to virtual check of possible algorithms for setting the load.